2022
DOI: 10.1136/bmjopen-2021-050821
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute pancreatitis prevention by the elimination of alcohol and cigarette smoking (REAPPEAR): protocol of a randomised controlled trial and a cohort study

Abstract: Background/objectivesAcute recurrent pancreatitis (ARP) due to alcohol and/or tobacco abuse is a preventable disease which lowers quality of life and can lead to chronic pancreatitis. The REAPPEAR study aims to investigate whether a combined patient education and cessation programme for smoking and alcohol prevents ARP.Methods and analysisThe REAPPEAR study consists of an international multicentre randomised controlled trial (REAPPEAR-T) testing the efficacy of a cessation programme on alcohol and smoking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…A meta-analysis by Platt et al showed that brief advice provided by nurses brings the most favorable outcomes, and Kaner et al also confirmed that a longer duration of counseling probably has no relevant additional effect [ 22 , 23 ]. There are several undergoing randomized clinical trials investigating the effectiveness of the psychological approach on alcohol or smoking habits [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis by Platt et al showed that brief advice provided by nurses brings the most favorable outcomes, and Kaner et al also confirmed that a longer duration of counseling probably has no relevant additional effect [ 22 , 23 ]. There are several undergoing randomized clinical trials investigating the effectiveness of the psychological approach on alcohol or smoking habits [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies and RCTs are needed to identify the adequate structure and frequency of BIs to achieve alcohol abstinence and minimize the risk of alcohol-induced RAP [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, the implementation of screening tools to identify patients who would benefit from whole-person interventions and implementing multicomponent behavioral interventions are likely to improve the management and QOL in CP. 12 Longitudinal data collection in prospective studies using multiple biomarkers such as brain imaging, quantitative sensory testing, assessment of psychosocial factors, and blood markers may predict progression of CP and aid in identifying patients suitable for whole-person interventions. Specific research methodologies and clinical trial designs to study interconnected systems (eg, machine learning methods, latent class/profile analysis, adaptive interventions) may be particularly pertinent in CP clinical trials.…”
Section: Whole-person Approach: Connections Across Biological Behavio...mentioning
confidence: 99%
“…According to Ahmed Ali et al , in a follow-up study of 669 AP patients, smoking represented the dominant risk factor for recurrent AP (RAP) and a combination of alcohol consumption and smoking was the main risk factor for the progression to CP 5. Therefore, cessation programmes and patient education are extremely important means to intervening and lowering the recurrence of AP and the progression to CP 6 7. However, total cessation and abstinence often seems impossible for patients and they do not even try.…”
mentioning
confidence: 99%